Flexible iron: disorder in the ironome brings order to protein structure and function - Vladimir N. Uversky; Vladimir N. Uversky; Gloria C. Ferreira; Gloria C. Ferreira; Gloria C. Ferreira (Frontiers in Molecular Biosciences)
Iron is one of the most abundant elements on earth. The most recognized role of iron in living organisms is its incorporation in the heme-containing protein hemoglobin, which is abundantly found in the red blood cells that facilitate the oxygen transportation throughout the body. In fact, about 70% of organism’s iron is found in hemoglobin. However, besides being essential for oxygen transport and serving as a crucial component of the molecular oxygen-carrying proteins hemoglobin and myoglobin, iron has a wide range of other biological functions. It is involved in numerous metabolic and regulatory processes and therefore is indispensable for almost all living organisms. Since iron enzymes are responsible for most of the redox metallo-catalysts, it is not surprising that 6.5% of all human enzymes are expected to be iron-dependent. Furthermore, iron-binding proteins account for about 2% of the entire proteome. The ironome encompasses heme-binding proteins, proteins binding individual iron ions, and iron–sulfur cluster-binding proteins. Although the structure-function relations of ordered iron-binding proteins are rather well understood, the prevalence and functionality of intrinsic disorder in iron-binding proteins remain to be evaluated. To fill this knowledge gap, in this study, we evaluate the intrinsic disorder of the human ironome. Our analysis revealed that the human ironome contains a noticeable level of functional intrinsic disorder, with most noticeable applications in protein-protein interactions, posttranslational modifications, and liquid-liquid phase separation.